T4 Increased reticular basement membrane thickness but NOT airway smooth muscle in endobronchial biopsies of severe preschool wheezers. (16th November 2010) - O'Reilly, R; Oates, T; Zhu, J; Jeffery, P K; Bush, A; Saglani, S
Abstract : Introduction: About a third of all children wheeze (Martinez, NEJM 1995), yet only half will develop asthma (Morgan, AJRCCM 2005). We know that increased reticular basement membrane (RBM) thickness, a feature of airway remodelling in older children with asthma, develops at 2–3 years of age in preschool severe recurrent wheezers (Saglani, AJRCCM 2007) but unlike older children (Regamey, AJRCCM 2008) nothing is known about any changes in airway smooth muscle (ASM) at pre-school age. Hypothesis: There is increased ASM and ASM infiltration by mast cells in preschool children. Methods: Endobronchial biopsies (EBx) were obtained from preschool children undergoing clinically indicated bronchoscopy from 2002 to 2005; severe, recurrent wheezers (n=47, median age 21.5 months) and non-wheezers (n=21, median age 19 months). Up to 12 (5 μm) sections were cut and stained with haematoxylin and eosin. ASM volume fraction was measured using point and line intersection counting (Regamey, AJRCCM 2008). A subgroup of children (n=33) had sections stained for mast cell tryptase. Area of subepithelium and smooth muscle were calculated using image analysis. Mast cells were expressed per area of subepithelium and ASM (Brightling, NEJM 2002). Results: ASM was present in EBx of 50 (73.5%) children, 17 controls (median age 17 months) and 33 wheezers (median age 21 months), with an average of 1.9 (range 1–5) sections with ASM per child. There was no difference in volume fraction of ASM, either indexed to volume of subepithelial tissue (p=0.52) or surface area of RBM (p=0.14), between wheezers and controls. There was no correlation between age and ASM in wheezers or controls. Submucosal mast cells were similar in wheezers (n=25, 139/mm 2 ) and controls (n=8, 121/mm 2 ) (p=0.5). No difference was found between wheezers and controls in the number of mast cells within ASM (p=0.17). Conclusion: Severe preschool wheezers have evidence of increased RBM thickness, but not increased ASM compared to age-matched non-wheezing controls. Since both are features of airway remodelling in school age asthma, this suggests ASM increases only after a longer duration of symptoms. These data highlight the potential to intervene during preschool years before airway remodelling is fully established to alter the natural history of asthma.